A Review on Casting Magnesium Alloys: Modification of Commercial Alloys and Development of New Alloys. Issue 12 (December 2016) - Pan, Fusheng; Yang, Mingbo; Chen, Xianhua
Abstract : The research and development status of casting magnesium alloys including the commercial casting alloys and the new types casting alloys are reviewed, with more attention to microstructure and mechanical properties of modified-AZ91, AM60 and WE43 alloys with various additions, and new types of low cost casting alloys and high strength casting alloys. The modification and/or refinement of Mg2 Si phase in Mg–Al–Si based casting alloys by various additions are discussed and new purifying technologies for casting magnesium alloys are introduced to improve the performance. The modified AZ81 alloy with reduced impurities is found to have the tensile strength of 280 ± 6 MPa and elongation of 16% ± 0.7%. The fatigue strength of AZ91D alloy could be obviously improved by addition of Ce and Nd. The Mg–16Gd–2Ag–0.3Zr alloy exhibits very high tensile and yield strengths (UTS: 423 MPa and YS: 328 MPa); however, its elongation still needs to be improved.